Production and characterization of calcium phosphates from marine structures: The fundamentals basics - (:unkn) unknown (Springer Science and Business Media, LLC, 2019)
Processes such as traditional wet chemical methods and heat and pressure-based hydrothermal methods are some of the important methods that has been used to produce hydroxyapatite (HAp), tricalcium phosphate (TCP) and other phosphate derivatives. Recently, new approaches such as ultrasonication (can be considered as a mechanical processing route) and hot-plating (heating element added to mechanical processing) were introduced. Using these new approaches, production for nanostructured calcium phosphate can be easily achieved. Traditionally, calcium phosphate-based compounds are produced using starting materials that contains calcium and phosphate. However, the use of marine structures as raw ingredients has been widely encouraged and their uses in the medical/surgical arena are creating new avenues such as in applications that support bone repair and regeneration. Primary sources of marine-based materials are numerous and includes corals, algae, cuttlefish, fish bones, sea urchin, sea snail shells, sponges, sea shells, foraminifera, barnacles, nacre, sea mussels and so on. Knowing other chapters in this book covers the review of these materials in more detail, therefore in this chapter, we aimed to give examples and review some of the new as well as traditional production routes and techniques used to characterize the physiochemical properties of the calcium phosphates produced are also examined. © Springer Nature Singapore Pte Ltd 2019.
Keywords: Bone; Calcium phosphates; Characterization; Hydroxyapatite; Marine sources; Nanostructures; Production routes; Sea shell